Discharge characteristics of fractured soft piezoelectric ceramics under repeated impact. Issue 15 (15th October 2020) - Wang, Ruizhi; Tang, Enling; Yang, Guolai; Han, Yafei; Chen, Chuang
Abstract: Pb1 · 0 [Zr0 · 49 Ti0 · 46 (Li0 · 25 Sb0.75 )0.05 ]O3 (PZT-5H) is easy to break under overload. To explore the electrical output characteristics of fractured PZTs when they are subjected to repeated impact, experiments were performed by using SHPB loading and testing system. The results show that the irregularity of internal defects for PZT has different breaking strengths. The breaking strength of PZT-5H in experiments varies from 30 MPa to 50 MPa. The electric displacement and stress can meet the classical piezoelectric equation without considering the influence of fracture on discharge, but the dynamic and quasi-static piezoelectric constants d33 are quite different. With the increase of stress rising rate, d33 increases gradually. Under different impact velocities, the relationship between electric displacement and stress peak is nonlinear; Whether it is electrical short-circuit or open-circuit, the influence of fracture on the electrical output is limited. The influence of crack caused by overload on discharge can be ignored when the electrode material does not be damaged.